Brain drain in Malaysia’s banking and finance industry: Causes, impacts, and strategies for talent retention - Kaushan, Sundarial; Yew, Jackie Zhi Dar; Yong, Shirley Li Yung; Lim, Terence Run Ce; Wai, Ru En (2024)
Brain drain refers to the phenomenon where professionals regardless of their industry in a country emigrating to other country to work due to many reasons such as better job opportunities, favourable salaries, better political stability and so forth. This phenomenon may lead to shortage of skilled professionals in their home country which will subsequently affect the country’s economy negatively. The primary objective of this study is to determine the factors influencing the intention of professionals in Malaysia banking and finance industry to work abroad. The relationships of career dissatisfaction, salary and compensation, and quality of life on intention to work abroad are analysed. Quantitative research method is applied as the methodology for this study. The primary data analysed in the study is collected via the application of online questionnaire known as Google Forms. In order to collect the data required, convenience sampling techniques under the nonprobability sampling technique is utilized. The reliability of the questionnaire is test via SPSS under Pilot test of 40 respondents. After determining the reliability of the questionnaire, the questionnaire is distributed to professionals under the banking and finance industry in Malaysia, including those students under banking and finance that planned to join the industry in future. The questionnaire received at total of 449 responses, where 413 of them are eligible for the study. The data collected is analysed thoroughly using SmartPLS 4, and described in the form of descriptive analysis, reliability test, convergent and discriminant validity analysis, and assessment of structural model. The results obtained reflects that career dissatisfaction, and quality of life are having significant relationship with the intention of professionals under Malaysia banking and finance industry to work abroad. While the relationship of career advancement abroad does not have mediating effect on the relationship of independent variables and dependent variable. In order for better results in future study, some limitations and recommendations are provided in the end of the study for future researchers.